Prolonged Time to Brake Following Lower Extremity Injuries. (5th April 2023) - Alejo, Andrew L.; Rascoe, Alexander; Kim, Chang-Yeon; Ren, Bryan O.; Hoffa, Matthew T.; Heimke, Isabella M.; Vallier, Heather A.
Abstract : Introduction: No guidelines exist for recommending return to driving. This study will examine time to brake (TTB) after lower extremity injuries versus in uninjured people. The potential effect of various types of lower extremity injuries on TTB will be measured. Methods: Patients with injuries to the pelvis, hip, femur, knee, tibia, ankle, and foot underwent testing using a driving simulator to assess TTB. Comparison was with a control group of uninjured people. Results: Two-hundred thirty-two patients with lower extremity injuries participated. The majority were in the tibia and ankle regions (47%). Mean TTB for control subjects was 0.74 seconds, compared with 0.83 for injured patients, noting a 0.09-second difference ( P = 0.017). Left-sided injuries averaged TTB of 0.80 seconds, right-sided injuries averaged TTB of 0.86 seconds, and bilateral injuries averaged TTB of 0.83 seconds, all prolonged versus control subjects. The longest TTB was exhibited after ankle and foot injuries (0.89 seconds) while the shortest was after tibial shaft fractures (0.76 seconds). Discussion: Any lower extremity injury caused a prolonged TTB compared with control patients. Left, right, and bilateral injuries all had longer TTB. Ankle and foot injuries experienced the longest TTB. Additional investigation is warranted to develop safe guidelines for return to driving.